PATRONAGE, UNION, AND PARTICIPATORY REALISM: READING ROMANS 6 THROUGH ASIAN EYES - Hamonangan Masasko Anthoni; Adi Prasetyo Wibowo; Damai Wijaya; David Samuel (CV Naskah Aceh, 2026)
This article proposes a rereading of Romans 6:1–14 through an Asian hermeneutical lens, arguing that the dominant forensic-juridical interpretation of Pauline soteriology reflects Reformation-era Western legal culture more than the Mediterranean patronage world in which Paul originally wrote. Drawing on social-scientific studies of first-century Mediterranean honor-shame dynamics and patron-client relations, alongside developments in Asian contextual theology, the article contends that Asian readers—shaped by relational, communal, and patronage-based social structures—intuitively access a participatory reading of Romans 6 that has been largely obscured in Western scholarship. Special attention is given to Romans 6:7, where the forensic verb δεδικαίωται (dedikaīōtai, “has been justified/freed”) appears within a participatory argument, demonstrating that Paul himself does not separate juridical declaration from existential transformation. The article proposes “participatory realism”—a framework that is real, performative, and sacramental—as a constructive alternative that emerges from both rigorous exegetical analysis and Asian hermeneutical sensibility.